Comparative study of efficacy of epidermal melanocyte transfer versus hair follicular melanocyte transfer in stable vitiligo - Navya Donaparthi; Ajay Chopra (Wolters Kluwer Medknow Publications, 2016)
Background: Vitiligo surgery has come up a long way from punch skin grafts to epidermal cell suspension and latest to the extracted hair follicle outer root sheath cell suspension (EHFORSCS) transplantation. The progressive development from one technique to the other is always on a quest for the best. In the latest development, EHFORSCS, which is an enriched source of follicular inactive melanocyte (melanocyte stem cells), seems to be a good addition to the prevailing cell-based therapies for vitiligo. However, it needs to be explored further in larger, clinical trials. Methodology: A total of 11 patients with sixty stable vitiligo sites attending dermatology outpatient department were included for the open-labeled, prospective, comparative study. The sites were sequentially distributed into two groups of thirty each. Sites of one group were subjected to epidermal melanocyte transfer (EMT) and the others to hair follicular melanocyte transfer (HFMT). Response to treatment was evaluated on the basis of degree of repigmentation; final evaluation of area of involvement was done after completion of 6 months. Results: At the end of 6 months, repigmentation >90% was observed in 83.33% patches of EMT group and 43.33% in HFMT group. Repigmentation >75% was observed in 90% of patches in Group A and 43.34% of patches in Group B, respectively. There was statistically significant difference in the overall pigmentation between these two groups. Conclusion: Both noncultured autologous epidermal cell suspension transfer and noncultured EHFORSCS transfer are safe and effective surgical modalities in the management of stable vitiligo though EMT has shown a better response in the present study. Outer root sheath cell suspension transfer is a novel, minimally invasive technique in its nascent stage in the surgical management of vitiligo which requires further larger clinical trials for evaluation of its efficacy.